Specifying the Content of Credentialing Examinations - Clauser, Amanda L.; Raymond, Mark (Testing in the Professions, 2017)
The purpose of content specifications is to articulate the important features of a test, including the knowledge, skills, and abilities (KSAs) to be covered, the format of the assessment tasks, the demands of those tasks, and the emphasis allocated to each of these areas within the examination. The task inventory is one of the most common task-oriented methods for defining the content domain for credentialing examinations. Data are collected from a broad sample of individuals using a survey, or questionnaire that outlines tasks or duties, actions, and decision points made by professionals. The task inventory is particularly useful for credentialing purposes as it can be used to identify actions, abilities, and knowledge that is important to successful practice across practice settings. In order to define KSAs and translate practice analysis data into test specifications, many approaches rely on a combination of input from subject matter experts (SMEs) and current practitioners, educators, and others with knowledge about the domain of practice.